Development of The Story Book “Negeri Hastinapura” to Instill Patriotism Value in Primary School Student - Komalasari, Mahilda Dea; Widyaningsih, Nina; Wihaskoro, Ahmad Mabruri (Proceeding International Conference on Science and Engineering, 2020)
The phenomenon of radicalism in Indonesia is still rife, such as the bombing of the church in Surabaya, the shootout with radicalist in Yogyakarta, are some examples of recent events of radicalism. Likewise, the events of radicalism in the world, the radical group ISIS is a group that often carries out acts of radicalism and ISIS propaganda that should be watched out so as not to damage peace in Indonesia. This shows that the importance of efforts to overcome radicalism, namely through the prevention of the development of radicalism. The background of this research is motivated by the importance of preventing radicalism from developing among primary school students through instilling the values of patriotism. The story book "Negeri Hastinapura" was chosen because wayang can be used as an educational tool, because it contains elements of truth, justice, purpose, obedience, loyalty, heroism, spiritual, psychological, philosophical and all aspects of human disposition and its problems (Tofani, 2013). “Negeri Hastinapura” is the country contained in the Mahabharata puppet story. This story book "Negeri Hastinapura" takes place when it is led by Prabu Yudistira, where the country is safe, peaceful, and the community is prosperous, so students can be taught exemplary values and instilling the values of patriotism. The development of the story book "Negeri Hastinapura" was designed using the development research (R&D) method using the subject of primary school students. The story book "Negeri Hastinapura" was tested in primary schools, SDIT Insan Utama, Yogyakarta. The results of the analysis of the value of patriotism showed that the t-test score was 5.350 with Sig. 0,000. This shows that there is a significant increase in the value of students’ patriotism between before and after learning using the story book "Negeri Hastinapura".